Probiotic bacteria from 10 different traditional Iranian cheeses: Isolation, characterization, and investigation of probiotic potential. Issue 6 (7th March 2022) - Afshari, Asma; Hashemi, Mohammad; Tavassoli, Milad; Eraghi, Vida; Noori, Seyyed Mohammad Ali
Abstract: In this study, 10 different traditional Iranian cheeses, which are still consumed by people in rural areas of Iran, were examined to isolate new strains of probiotic bacteria. Isolated bacteria were identified by 16s rRNA gene amplification and subjected to series of in vitro tests to find out their probiotic potential. A total of 2345 colonies were collected and 465 of them were confirmed as lactic acid bacteria (LAB), of which Lactiplantibacillus plantarum, Lactobacillus bulgaricus, and Lacticaseibacillus casei were the top three isolated bacteria. Among the different species of LAB isolated in this study, Lactip . plantarum was the most isolated species, and seven isolates had the significant criteria for being a probiotic strain than other isolates indicating the most adaptable properties of this species. Lactiplantibacillus plantarum was the most resistant bacteria in the bile resistance test and was also the most durable bacteria in gastrointestinal conditions, for example, acidic environment (pH = 2.5) and trypsin. In contrast, Lacticaseibacillus casei was the most susceptible bacterial strain. Lactobacillus rhamnosus showed the most antibacterial effect against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa . This study showed that probiotic strains isolated from local cheeses could be considered as suitable biopreservatives and used as specific starter cultures for the production of functional cheeses. Abstract : In this study, efforts have been made to isolate new lactic acid bacteria. Lactiplantibacillus plantarum was the most isolated species and seven isolates had the major criteria for being a probiotic strain. Lactip . plantarum was the most resistant bacteria in bile resistance test and was also the most durable bacteria in gastrointestinal conditions, for example, acidic environment (pH = 2.5) and trypsin. This study showed that probiotic strains isolated from local cheeses can be considered as suitable biopreservatives and used as specific starter cultures for the production of functional cheeses.